Respuesta :
4x^2 + x + 3 = 0
x = [-1 +/- sqrt (1^2 - 4 * 4 * 3)] / 8 = - 1 +/- sqrt ( --47) / 8
= ( - 1 +/- sqrt47i) / 8 = -0.125 + 0.857i , -0.125 - 0.857i
x = [-1 +/- sqrt (1^2 - 4 * 4 * 3)] / 8 = - 1 +/- sqrt ( --47) / 8
= ( - 1 +/- sqrt47i) / 8 = -0.125 + 0.857i , -0.125 - 0.857i
Hello there :)
Check the picture below for the answer.
Let me know if you have questions about my answer.
Best of luck!
Check the picture below for the answer.
Let me know if you have questions about my answer.
Best of luck!
![Ver imagen garydesir1](https://us-static.z-dn.net/files/dde/614d1f38c1c33eeaca5efc1010cd941b.png)
![Ver imagen garydesir1](https://us-static.z-dn.net/files/db8/a05b854418a7e8d822a4b9779769a871.png)